Magnum landscape (Phaidon, 2005)
"In the tradition of great Magnum books this publication brings together work by the finest photographers of our time. For 50 years Magnum photographers, through commissions and their personal work, have produced images that comment on the state of the world. In photographing the landscape they are not just spectators but participants, aware that the land itself has been shaped by man, and that the very notion of a landscape depends on a human viewpoint. As each photographer records, interprets and finds a unique personal style, the variations on a theme are endless - landscapes of war, of agriculture, of industry, of cities and motorways, of desolation, celebration and tranquillity. The photographs gathered in this book invite us to rediscover landscape, and urge us to think more profoundly about the planet earth."--BOOK JACKET.
Originally published: 1996
Keywords: Magnum Photos Inc.; Landschaft -- Motiv; Fotografie; Landscape photography; Landscapes / Pictorial works; Landscapes; Foto's; Magnum; Landschappen; Fotografi / bildverk; Landskapsfotografi; Pictorial works; Bildband